2023
DOI: 10.1002/anie.202218128
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Degradation of PD‐L1 and Activation of the STING Pathway by Carbon‐Dot‐Based PROTACs for Cancer Immunotherapy

Abstract: Proteolysis targeting chimeras (PROTACs) technology is an emerging approach to degrade disease‐associated proteins. Here, we report carbon‐dot (CD)‐based PROTACs (CDTACs) that degrade membrane proteins via the ubiquitin‐proteasome system. CDTACs can bind to programmed cell death ligand 1 (PD‐L1), recruit cereblon (CRBN) to induce PD‐L1 ubiquitination, and degrade them with proteasomes. Fasting‐mimicking diet (FMD) is also used to enhance the cellular uptake and proteasome activity. More than 99 % or 90 % of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…By depleting HER2, GNCTACs efficiently inhibited the growth of SKBR3 tumors with FMD treatment. Since the ubiquitination system is distributed in the cytoplasm, membrane proteins are not considered ideal targets for PROTACs. Our results showed that GNCTACs could be used for membrane protein degradation with high efficiency.…”
Section: Introductionmentioning
confidence: 91%
“…By depleting HER2, GNCTACs efficiently inhibited the growth of SKBR3 tumors with FMD treatment. Since the ubiquitination system is distributed in the cytoplasm, membrane proteins are not considered ideal targets for PROTACs. Our results showed that GNCTACs could be used for membrane protein degradation with high efficiency.…”
Section: Introductionmentioning
confidence: 91%
“…At present, VHL E3 ligand has been widely and successfully applied in the design and synthesis of PROTAC as one of the most commonly used E3 ligands (Table 1). 13,17,18,142–154 …”
Section: Vhl Ligands and Their Utilizations In Protacs For Cancer Dru...mentioning
confidence: 99%
“…Carbon-dots, a new carbon-based quasi-spherical nanomaterial with diameters below 10 nm, good biocompatibility and photoluminescence, have been conjugated with PD-L1 and E3 ligase targeting probes [24]. After injection into tumor-bearing animals, caloric restriction enhanced the uptake of these modified carbon-dots by PD-L1-expressing cells resulting in increased proteasome activity and almost complete PD-L1 ubiquitination and degradation, followed by activation of dendritic and cytotoxic T cells and inhibition of tumor growth without evident systemic toxicity [24].…”
Section: Effects Of Caloric Restriction In Preclinical Cancer Modelsmentioning
confidence: 99%